A Place for Integration: Refugee Experiences in Two English Cities. Issue 5 (10th May 2015) - Platts‐Fowler, Deborah; Robinson, David; Phillips, Deborah; Robinson, David
Abstract This paper seeks to inject an appreciation of place into analysis of refugee integration. A framework of integration sensitive to interactions between people and places is operationalised to facilitate the systematic comparison of the refugee integration process in different places. In particular, this paper explores variations in key indicators of integration within a cohort of refugees arriving into the UK from the same country of origin (Iraq), at the same time, granted the same legal status and afforded a similar package of support and assistance but settled in two cities in England (Hull and Sheffield). Variations in the integration experiences of refugees in the two cities are spotlighted and related to the contextual, compositional, and collective aspects of the places into which they were settled. The findings highlight the importance of recognising that refugee integration is grounded and embodied in space and place and that despite proceeding under the same general operative processes, can evolve in distinctive ways in different places. Copyright © 2015 John Wiley & Sons, Ltd.